Rhodium‐catalyzed Insertion Reaction of Perfluoroarenes into Unprotected Peptide Disulfides. Issue 9 (27th July 2022) - Fukumoto, Kohei; Yazaki, Masana; Arisawa, Mieko
Abstract: The method of rhodium‐catalyzed insertion reaction of perfluoroarenes between unprotected peptide cystine disulfides is developed. The method is applicable to peptides containing amino acids such as Ser, Asn, Asp, and Lys without affecting hydroxy, primary amine, carboxylic acid, and amide groups. The reaction does not require a base and proceeds under acidic, neutral, and basic conditions. No free thiols are detected, and the reaction is considered to proceed via rhodium thiolates. A crossover experiment shows minimal scrambling of organothio groups. Abstract : A method of rhodium‐catalyzed insertion reaction of perfluoroarenes between unprotected peptide cystine disulfides is developed. The method is applicable to peptides containing amino acids such as Ser, Asn, Asp, and Lys without affecting hydroxy, primary amine, carboxylic acid, and amide groups.